2020
DOI: 10.2144/btn-2019-0168
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Loop-mediated Isothermal Amplification Assay for Rapid Detection of Fusarium Circinatum

Abstract: Fusarium circinatum is the causal agent of pitch canker, a lethal disease of pine and other conifers. Since F. circinatum is a quarantine organism, its timely detection could efficiently prevent its introduction into new areas or facilitate spread management in already infected sites. In this study, we developed a sequence-specific probe loop-mediated isothermal amplification (LAMP) assay for F. circinatum using a field-deployable portable instrument. The assay was able to recognize the pathogen in host tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The LAMP-based assays developed in this work were capable of rapidly identifying these three pathogens in less than 30 min (Figure 1); a substantial improvement compared to the currently available DNA-based diagnostics for these species [45][46][47][48]. These assays also have the potential to be deployable in-field, directly at point-of-care with the use of portable devices developed for supporting LAMP reactions (e.g., Genie ® II and III by OptiGene Limited, Horsham, UK) [55,56,59]. To the best of our knowledge, there are no published LAMP-based assays targeting L. acicola and D. pini, while for D. septosporum a LAMP-based assay has been recently published [60].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The LAMP-based assays developed in this work were capable of rapidly identifying these three pathogens in less than 30 min (Figure 1); a substantial improvement compared to the currently available DNA-based diagnostics for these species [45][46][47][48]. These assays also have the potential to be deployable in-field, directly at point-of-care with the use of portable devices developed for supporting LAMP reactions (e.g., Genie ® II and III by OptiGene Limited, Horsham, UK) [55,56,59]. To the best of our knowledge, there are no published LAMP-based assays targeting L. acicola and D. pini, while for D. septosporum a LAMP-based assay has been recently published [60].…”
Section: Discussionmentioning
confidence: 88%
“…Efforts should also be directed toward validating the developed assays for use at point-of-care on portable devices and using crude DNA extracts, as this has already been successfully performed in numerous pathosystems, including forest pests and pathogen species such as Heterobasidion irregulare Garbel and Otrosina, Hymenoscyphus fraxineus (T. Kowalski) Baral, Queloz and Hosoya, Phytophthora spp, Raffaelea lauricola Harrington, Fraedrich and Aghayeva, Xylella fastidiosa Wells, Raju, Hung, Weisburg, Parl and Beemer, Ceratocystis spp., and Fusarium spp. [54,[56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional LAMP (cLAMP) and a quantitative LAMP (qLAMP) assays were performed to diagnose a quarantine fungal pathogen Fusarium circinatum that causes pitch canker in pine and other conifers. LAMP probes targeting TEF-1α revealed that qLAMP tests had higher specificity than cLAMP for the detection of F. circinatum ( Stehliková et al., 2020 ). A widespread pathogen, Sclerotinia sclerotiorum , with a broad host range including rape seed, was detected using a LAMP assay targeting Ssos5 and a visualizing indicator hydroxynaphthol blue (HNB) for detection.…”
Section: Molecular Tools For Detection Of Fungimentioning
confidence: 99%
“…Molecular assays based on LAMP have been developed to diagnose a range of parasitic infections in both humans and animals (e.g., malaria, leishmaniasis, and cysticercosis) [ 24 ]. Recently, several LAMP tests have also been devised for the identification of invasive plant pathogens [ 25 , 26 , 27 , 28 ] and insect pests [ 29 , 30 , 31 ], both for field applications and in the laboratory. The LAMP technique is a robust and suitable technique for in situ application owing to its low infrastructure requirements and minimal operator training [ 32 ].…”
Section: Introductionmentioning
confidence: 99%